First Bites—Why, When, and What Solid Foods to Feed Infants - Borowitz, Stephen M. (Frontiers in Pediatrics, 2021)
Humans are the only mammals who feed our young special complementary foods before weaning and we are the only primates that wean our young before they can forage independently. There appears to be a sensitive period in the first several months of life when infants readily accept a wide variety of tastes and this period overlaps with a critical window for oral tolerance. As a result, infants should be exposed to a wide variety of flavors while mother is pregnant, while mother is nursing and beginning at an early age. There also appears to be a sensitive period between three and nine months when infants are most receptive to different food textures. There remains debate about when it is best to begin introducing solid foods into an infant’s diet however the available evidence suggests that provided the water and food supply are free of contamination, and the infant is provided adequate nutrition, there are no clear contraindications to feeding infants complementary foods at any age. There is emerging evidence that introduction of solid foods into an infant’s diet by four months may increase their willingness to eat a variety of fruits and vegetables later in life, decrease their risk of having feeding problems later in life, and decrease their risk of developing food allergies, and the early introduction of solid foods into an infant’s diet does not appear to increase their risk of obesity later in childhood.